Trueness and Precision of Three-Dimensional Digitizing Intraoral Devices - Hussam Mutwalli; Michael Braian; Deyar Mahmood; Christel Larsson (Hindawi Limited, 2018)
Aim. To measure the trueness and precision under repeatable conditions for different intraoral scanners (IOSs) when scanning fully edentulous arch with multiple implants. Materials and Methods. Three IOSs and one industrial scanner were used to scan one edentulous master cast containing five implant scan bodies and three spheres. The cast was scanned thirty times with each scanner device. All scans were analyzed in the inspect software, and three-dimensional locations of the implants and the interarch distance between the spheres were measured. The values were compared to measurements made with one coordinate measuring machine (true value). One-way ANOVA was used to calculate the differences between IOSs and in comparison with the true value. Results. Significant differences were found between all IOSs. For the implant measurements, Trios 3 had the lowest trueness (≤114 μm), followed by Trios 3 mono (≤63 μm) and Itero element (≤−41 μm). Trios had the lowest precision (≤135 μm), followed by Itero element (≤101 μm) and Trios 3 mono (≤100 μm). With regard to the interarch distance measurements, Trios 3 had the lowest trueness (≤68 μm), followed by Trios 3 mono (≤45 μm) and Itero element (≤40 μm). Trios 3 had the lowest precision (≤206 μm), followed by Itero element (≤124 μm) and Trios 3 mono (≤111 μm). Conclusion. The results from this in vitro study suggest that precision is low for the tested IOS devices when scanning fully edentulous arches with multiple implants.